Major haemorrhage protocols. (6th March 2018) - Booth, C.; Allard, S.
Abstract : Major haemorrhage protocols are aimed at optimizing the care of patients suffering life‐threatening bleeding. They should clearly set out the responsibilities of all of the staff involved including clinical and laboratory teams and other support staff with explicit lines of communication to support a prompt response without delays. The emphasis is on ready access to blood and components to limit coagulopathy in conjunction with definitive methods of controlling haemorrhage. High‐quality evidence for the early use of tranexamic acid strongly supports the inclusion of this drug in protocols for trauma and obstetric haemorrhage. Although national and international guidelines recommend the use of MHPs, they are not without drawbacks. Much of the evidence for their use comes from studies of trauma haemorrhage, and although the principles are widely applied to other clinical settings, there is a lack of data to guide practice in bleeding from other causes. Initial empirical replacement of red cells and plasma in fixed ratios largely based on experience from the military is now common in trauma, but this approach might result in overtreatment of some patients. As hypofibrinogenaemia is a poor prognostic factor, the inclusion of early fibrinogen replacement deserves attention and is the subject of active research. Further studies are examining the use of targeted transfusion strategies based on near‐patient testing, use of whole blood and chilled platelets, expanding indications for tranexamic acid and component use in the prehospital setting. MHPs should be reviewed regularly following local audit with ongoing update to reflect new research findings.